The causal relationship between 91 inflammatory cytokines and Gestational Diabetes Mmellitus: A bidirectional two-sample Mendelian randomization study - Pan, Lele; Hong, Shuzhen; Li, Yuhan; Yuan, Li; Zhao, Lina; Wen, Jiying (Diabetes research and clinical practice, 2024)
Gestational Diabetes Mellitus (GDM) poses significant risks to maternal and fetal health, yet its precise etiology remains unclear. Observational studies have demonstrated a link between specific inflammatory cytokines and the occurrence of GDM, but the causal relationships remain uncertain. Utilizing publicly accessible genetic data, we performed a bidirectional two-sample mendelian randomization (MR) analysis to elucidate the causal association between 91 inflammatory cytokines and GDM. Sensitivity analysis was carried out to evaluate the robustness, heterogeneity, and potential presence of horizontal pleiotropy within the results. Elevated levels of Interleukin-7 (IL7) and Neurturin (NRTN) (OR=1.104, 95 % CI=1.003–1.216, p = 0.042; OR=1.102, 95 % CI=1.023–1.187, p = 0.010), along with decreased levels of Glial cell line-derived neurotrophic factor (GDNF), Interleukin-12 subunit beta (IL12β), and Interleukin-20 (IL20) (OR=0.911, 95 % CI=0.849–0.979, p = 0.010;OR=0.955, 95 % CI=0.916–0.996, p = 0.033; OR=0.892, 95 % CI=0.819–0.971, p = 0.008), are associated with increased GDM risk. Additionally, GDM occurrence correlates with increased Matrix metalloproteinase-10 (MMP-10) and decreased Interleukin-20 receptor subunit alpha (IL-20Rα) levels (OR=1.042, 95 % CI=1.002–1.084, p = 0.038; OR=0.949, 95 % CI=0.909–0.992, p = 0.021). Sensitivity analyses detected no significant heterogeneity or pleiotropy. This study has clarified the causal link between inflammatory cytokines and GDM, thereby enhancing our comprehension of the potential mechanisms involved in GDM pathogenesis. These findings offer new insights into the etiology, diagnosis, and therapeutic strategies for GDM.